THE BEHAVIOR OF BUREAUCRACY OFFICERS IN INTERNAL SERVICES AT THE MINISTRY OF RELIGIOUS AFFAIRS OF POHUWATO REGENCY - Rinda Kohongia; Darman; Warno Panigoro (LP2M Universitas Bina Mandiri Gorontalo, 2023)
The purpose of this research is 1) the behaviour of bureaucratic officer in internal services within the Ministry of Religion Affairs of Pohuwato Regency; 2) factors that influence the behaviour of bureaucratic officer in internal services within the Ministry of Religion Affairs of Pohuwato Regency. The approach of this research is qualitative. Data collection techniques through observation, interview guidelines and documentation. Furthermore, the data analysis method used is data reduction, data presentation and conclusions. The results of the research show that 1) the behaviour of bureaucratic officer in internal services within the Ministry of Religion Affairs of Pohuwato Regency is concern behaviours, disciplinary behaviour and responsible behaviour still need to be improved. Seen from the concern behaviour, the bureaucratic officer has a concern attitude as evidenced by their empathy for service users. Meanwhile, seen from the responsibilities, there are still employees who do not have a responsibility attitude, so that, they find a long duration of time in completing work due the officers often leaving the room when the service process is running. Go home early and the dress code is sometimes not followed; 2) Factors that inhibit the behaviour of bureaucratic officer in internal services within the Ministry of Religion Affairs of Pohuwato Regency include human resources and the availability of facilities and infrastructure